Promoting and managing international investment : towards an integrated policy approach - VanDuzer, J. Anthony (John Anthony), 1958-; Leblond, Patrick (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book provides an overview of international investment policy and policy-making drawing upon perspectives from law, economics, international business and political science. International investment is a complex phenomenon with significant effects worldwide. Developing effective policies and strategies to attract investment in sufficient quantities and marshal it to contribute to sustainable development is a critical challenge for governments at all levels. The book's interdisciplinary approach provides fresh insights into the mix of policy options available to governments seeking investment to support their country's (or region's) development. As well as identifying ways to effectively design, implement and assess policies to attract foreign investment, it explores how to manage foreign investment's effects. Various dimensions of international investment policy are discussed, including: benefits and costs (economic, environmental, social and political) of foreign investment, the significance of global value chains, state-owned enterprises and sovereign wealth funds, and the role of tax policy, investment promotion and policy advocacy, location branding, investment treaties, and national security considerations. Through its contributions to a new inter-disciplinary understanding of international investment policy-making, this book will benefit students and scholars working in areas such as international business, international economic law, international economics, development economics, international development and international political economy as well as being a valuable resource for policy-makers"--
Introduction to International Investment Policy and Rationale for an Interdisciplinary Approach / J Anthony VanDuzer, Patrick Leblond, and Stephen Gelb -- Trade and Foreign Direct Investment in the 21st Century / Ari Van Assche -- Actors, Institutions, and Policy in Host Countries / Krista Nadakavukaren Schefer -- State-Owned Enterprises and Sovereign Wealth Funds : An Economic Assessment / Steven Globerman, Phillip Hensyel, and Daniel Shapiro -- The Economics of Foreign Direct Investment and International Investment Agreements / Eugene Beaulieu and Kelly O'Neill -- Attracting Foreign Direct Investment : Location Branding and Marketing / Leila Hamzaoui Essoussi, Nicolas Papadopoulos, and Alia El Banna -- FDI Policy Advocacy and Investor Targeting / Matthew Durban -- Tax Competition as an Investment Promotion Tool / Allison Christians and Marco Garofalo -- National Security and the Political Economy of International Investment Policy / Patrick Leblond and Sébastien Labrecque -- International Investment Agreements / Lukas Vanhonnaeker -- Investor-State Dispute Settlement J Anthony VanDuzer and Patrick Dumberry -- Social and Environmental Issues in Foreign Direct Investment : A Legal and Policy Perspective Lorenzo Cotula -- Moving Beyond Disciplinary Silos : Toward an Integrated Approach to International Investment Policy / J Anthony VanDuzer, Patrick Leblond, and Stephen Gelb.
Includes bibliographical references and index.
Keywords: Investments, Foreign -- Law and legislation; Investments, Foreign (International law); Investments, Foreign